INVENTARISASI TUMBUHAN PENGHASIL PEWARNA ALAMI DI KEBUN RAYA CIBODAS - Muhammad Efendi; Intan Gresia Hapitasari; Rustandi Rustandi; Ateng Supriyatna (Bumi Lestari Journal of Environment, 2016)
Cibodas Botanic Garden, as ex situ conservation areas, preserves living materials ofthe wet mountains flora. Recently, bioprospecting study for dye in this areas has not yetbeen done. Therefor, the aim of this study was to inventory of natural dye in Cibodas BotanicGarden. Sampel were collected by exploration methods. Parts of plants, kinds of color andits chemical compound were recorded based on observation, interview with nurseries andliterature study. A total of 122 species that belongs to 57 families were potentially source asnatural dye, 23 of them has been traditionally used as natural dye in the various places inIndonesia. The plant family of Fabaceae, Rosaceae, Symplocaceae, and Myrtaceae are themost families that used as a source of dye. The color can be produce are ranging from red,purple, yellow, black, brown, green, blue, and orange. The plant organs used as a source ofdye are roots, stems, leaves, flowers, and fruit. Begonia semperflorens,Berberis nepaulensis,B.fortunei, Symplocosspp., Liquidambar formosana, andDiospyros kaki were potentially fornatural dye, as reported from other countries.